What is known about the impact of hypertension on the course of COVID-19 - Marina V. Moiseeva; Natalia V. Bagisheva; Anna V. Mordyk; Ekaterina G. Dzhusoeva; Ekaterina P. Antipova; Egor D. Marchenko (LLC "MEDIAFORMAT", 2022)
The aim of this work was an attempt to systematize the data available in the available literature and the course of coronavirus infection (coVId-19) in patients with arterial hypertension. It is known that hypertension is the most common disease, especially among older and elderly people. As predictors of an unfavorable course or progression of coronavirus infection, the authors indicate age, the level of increase in systolic blood pressure, as a predictor of vascular wall stiffness and endothelial dysfunction, and angiotensin-converting enzyme also plays a separate role. The lack of consensus on the impact of arterial hypertension on the course of coVId-19 requires a study of both hypertension itself and the components of antihypertensive therapy on the prognosis of the disease.